Al-Radīkālīyah al-Islāmīyah: Afkāruhā wa Ḥarakātuhā fī Indūnīsīyā al-Ma’āṣir - Tasman, Tasman (Studia Islamika, 2009)
This article endeavors to explain the notion of radicalism in the context of Islamic movements in Indonesia. Of late, radicalism has become a subject of debate among religious groups, especially radical religious movements such as the FPI (Front Pembela Islam, Islamic Defenders' Front) and the Laskar Jihad (Holy War Fighters). One of the issues debated is whether the term 'radical' is appropriate and indeed reflects their characteristics. Or, what is the right term to use for these groups. An Islamic movement, as one variant of social movements, is a collective first by an Islamic group to use Islamic teaching's norms and values as the foundation of economic, social, cultural and political life. In this context, Islam is not merely understood as a doctrine that regulates relations between man and God, but also as the basis of political life and as the foundation of the state.DOI: 10.15408/sdi.v16i1.492